Cell Surface Adhesins, Exopolysaccharides and the Por (Type Ix) Secretion System of Flavobacterium Johnsoniae - (:unkn) unknown (My University, 2013)
Flavobacterium johnsoniae, a member of the phylum Bacteroidetes, crawls rapidly over surfaces. Cell movement is thought to result from the action of the gliding motor, composed of Gld proteins, on the cell-surface adhesin SprB. Cells lacking SprB are partially defective in motility. Transposon mutagenesis of an sprB mutant resulted in the identification of remA, which encodes a motility adhesin that is partially redundant with SprB. Cells lacking SprB and RemA had more severe motility defects than did cells lacking just SprB. RemA moves on the cell-surface with a speed of 1 to 2 micrometer per sec, similar to SprB. RemA contains a lectin domain that enables it to interact with exopolysaccharides secreted by the cells. RemA-exopolysaccharide interaction resulted in the formation of cell-aggregates. Cells lacking polysaccharide biosynthesis and transport proteins RemC, Wza and Wzc failed to form aggreagates. It appears that as cells move, they pave their own `roads' with exopolysaccharide. Mobile cell-surface adhesins like RemA adhere to these `roads' and help in motility of the cell. Recent results suggest that some proteins required for gliding are components of a novel protein secretion system, the Type IX Bacterial Protein Secretion System (T9SS). The T9SS was initially called the Por Secretion System. T9SSs are found in all gliding bacteroidetes, and in many nongliding bacteroidetes, such as the periodontal pathogen Porphyromonas gingivalis, but they are apparently not found outside of the phylum Bacteroidetes. GldN, SprE, and SprT were previously shown to be components of the F. johnsoniae T9SS. Here we show that GldK, GldL, GldM, and SprA, are also components of this secretion system. The F. johnsoniae T9SS is required for secretion of SprB and RemA, and is thus needed for motility. Other proteins required for F. johnsoniae gliding, such as GldA, GldF, GldG (which form an ABC transporter complex), and GldB, GldD, GldH, GldI, and GldJ, may interact with the T9SS. Mutations in the genes encoding any of these proteins resulted in apparent instability of the T9SS protein GldK, and thus loss of T9SS function. The gliding motility proteins and the T9SS of F. johnsoniae appear to be intertwined. Strains that produced truncated GldJ proteins were isolated that had normal T9SS function but were defective in motility. Further analysis of these strains may enable us to untangle gliding motility from protein secretion.
Keywords: Cell Surface Adhesins; Flavobacterium Johnsoniae; Gld Protein; PorSS; RemA; Type IX